A Simple, Reproducible and Low-cost Simulator for Teaching Surgical Techniques to Repair Obstetric Anal Sphincter Injuries - Roxana Knobel; Lia Karina Volpato; Liliam Cristini Gervasi; Raquel de Almeida Viergutz; Alberto Trapani Júnior (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2018)
Abstract Objective To describe and evaluate the use of a simple, low-cost, and reproducible simulator for teaching the repair of obstetric anal sphincter injuries (OASIS). Methods Twenty resident doctors in obstetrics and gynecology and four obstetricians participated in the simulation. A fourth-degree tear model was created using lowcost materials (condom simulating the rectal mucosa, cotton tissue simulating the internal anal sphincter, and bovine meat simulating the external anal sphincter). The simulator was initially assembled with the aid of anatomical photos to study the anatomy and meaning of each component of the model. The laceration was created and repaired, using end-to-end or overlapping application techniques. Results The model cost less than R$ 10.00 and was assembled without difficulty, which improved the knowledge of the participants of anatomy and physiology. The sutures of the layers (rectal mucosa, internal sphincter, and external sphincter) were performed in keeping with the surgical technique. All participants were satisfied with the simulation and felt it improved their knowledge and skills. Between 3 and 6 months after the training, 7 participants witnessed severe lacerations in their practice and reported that the simulation was useful for surgical correction. Conclusion The use of a simulator for repair training in OASIS is affordable (low-cost and easy to perform). The simulation seems to improve the knowledge and surgical skills necessary to repair severe lacerations. Further systematized studies should be performed for evaluation.